Bioavailability and biotransformation of linolenic acid from basil seed oil as a novel source of omega-3 fatty acids tested on a rat experimental model. Issue 14 (22nd June 2022) - Martínez, Rosario; Mesas, Cristina; Guzmán, Ana; Galisteo, Milagros; López-Jurado, María; Prados, José; Melguizo, Consolación; Bermúdez, Francisco; Porres, Jesus M.
Abstract : Basil seed oil is a good source of α-linolenic acid that did not induce adverse effects in vivo, exhibiting high bioaccessibility, increased ALA, and decreased content of pro-inflammatory precursor arachidonic acid in plasma, liver and erythrocytes. Abstract : Basil is an aromatic herb with a high concentration of bioactive compounds. The oil extracted from its seeds is a good source of α-linolenic acid (ALA) and also provides substantial amounts of linoleic acid (LA). This study aimed to test the bioavailability of the oil derived from basil seeds and its effects on different physiological parameters using 7–15% dietary inclusion levels. Furthermore, the assimilation of LA and ALA and their transformation in long-chain polyunsaturated fatty acids (LC-PUFAs) have been studied. Digestive utilization of total fat from basil seed oil (BSO) was high and similar to that of olive oil used as a control. Consumption of BSO resulted in increased LA and ALA levels of the plasma, liver, and erythrocyte membrane. In addition, the transformation of LA to arachidonic acid (ARA) was decreased by the high dietary intake of ALA which redirected the pathway of the Δ-6 desaturase enzyme towards the transformation of ALA into eicosapentaenoic acid (EPA). No alterations of hematological and plasma biochemical parameters were found for the 7 and 10% dietary inclusion levels of BSO, whereas a decrease in the platelet count and an increase in total- and HDL-cholesterol as well as plasma alkaline phosphatase (ALP) were found for a 15% BSO dose. In conclusion, BSO is a good source of ALA to be transformed into EPA and decrease the precursor of the pro-inflammatory molecule ARA. This effect on the levels of EPA in different tissues offers potential for its use as a dietary supplement, novel functional food, or a constituent of nutraceutical formulations to treat different pathologies.